Answer:
The expression to solve the golfer's score is X = A + B + C
The golfer's score is 0 (The golfer is at par)
Explanation:
The given information are;
The score the golfer must have = 0
The score, A, the golfer has on the first hole = +4
The score. B, the golfer has on the second hole = -3
The score. C, the golfer has on the third hole = -1
Therefore, the expression to calculate the golfer's score, X, is given as follows;
The golfer's score = The score the golfer has on the first hole + The score the golfer has on the second hole + The score the golfer has on the third hole
The expression to solve the golfer's score is given as follows;
X = A + B + C
The golfer's score = 4 - 3 - 1 = 0
The golfer's score = 0.